2019
DOI: 10.3906/sag-1803-13
|View full text |Cite
|
Sign up to set email alerts
|

The role of hepcidin, GDF15, and mitoferrin-1 in iron metabolism of polycythemia vera and essential thrombocytosis patients

Abstract: Background/aim: GDF15, hepcidin and mitoferrin-1 (mfrn-1) are proteins involved in systemic iron regulation. There are no studies in the literature demonstrating the serum mfrn-1 levels in polycythemia vera (PV) and essential thrombocythemia (ET) patients. The aim of this study was to investigate GDF15, hepcidin and mfrn-1 levels in PV and ET patients. Materials and methods: Ten PV, 17 ET patients, and 27 healthy controls (HCs) were enrolled. GDF15, hepcidin and mfrn-1 values were measured with enzyme-linked i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…We hypothesised that in PV, where patients develop iron deficiency and have increased erythropoietic drive, hepcidin would be suppressed. However, this was not the case in our PV mouse model, a finding that recapitulates clinical studies that demonstrate hepcidin levels in newly diagnosed PV patients are comparable to healthy controls 62, 63 . Our data suggest that in PV, hepcidin may be upregulated by inflammation.…”
Section: Discussionsupporting
confidence: 81%
“…We hypothesised that in PV, where patients develop iron deficiency and have increased erythropoietic drive, hepcidin would be suppressed. However, this was not the case in our PV mouse model, a finding that recapitulates clinical studies that demonstrate hepcidin levels in newly diagnosed PV patients are comparable to healthy controls 62, 63 . Our data suggest that in PV, hepcidin may be upregulated by inflammation.…”
Section: Discussionsupporting
confidence: 81%
“…IL6 [1383], CSF3 [1384], SOCS3 [1385], CCL3 [1386], CCL5 [1387], VCAM1 [1388], CCL2 [1387], CXCL12 [1389], KLF10 [1390], FRZB (frizzled related protein) [1391], DUSP1 [1392], IL1B [1393], CCL11 [1394], LMNA (lamin A/C) [1395], WIF1 [1396], IL1RN [1397], IFNG (interferon gamma) [1398], CX3CL1 [1399], BMP2 [1400], CDKN1A [1401], BMP4 [1402], ICAM1 [1403], CD34 [1404], IL33 [1405], FASLG (Fas ligand) [1406], KDM6B [1407], TNF (tumor necrosis factor) [1408], GDF15 [1409], IL2 [1410], INPP4B [1411], FABP4 [1412], CYP2C19 [1413], CXCR4 [1414], DKK2 [1415], PLCB4 [1416], ANXA1 [1417], DUSP6 [1418], CORIN (corin, serine peptidase) [1419], F8 [1420], DDIT4 [1421], IL1R2 [1422], S100A4 [1417], CTSL (cathepsin L) [1423], PTX3 [1424], EFNB1 [1425], MCF2L [1426], FZD4 [1427], CCL26 [1428], PHGDH (phosphoglycerate dehydrogenase) [1429] and FDPS (farnesyl diphosphate synthase) [1430] have been identified as predictive biomarkers of osteoporosis. IL6 [1431], SOCS2 [1432], SOCS3 [1432], DUSP1 [1433], MLF1 [1434], EPHA2 [1435], CD34 [1436], IL33 [1437], GDF15 [1438], IL2 [1439], CD177 [1440], G6PD [1441], NFE2 [1442], PTX3 [1443], IDH1 [1444], MPO (myeloperoxidase) [1445] and KLK1 [1446] might be associated with the pathogenesis of polycythemia. The abnormal expression of IL33 [1447] and TNF (tumor necrosis factor) [1448] contributes to the pneumothorax.…”
Section: Discussionmentioning
confidence: 99%
“…Hepcidin production could be a defense mechanism against erythroid activity. This hypothesis remains inconclusive as other authors have observed normal hepcidin levels [24]. Third, the physiologically hypoxic intestinal lumen promotes iron absorption independently of hepcidin.…”
Section: Iron Deficiency In Polycythemiamentioning
confidence: 94%